2017
DOI: 10.1155/2017/3824276
|View full text |Cite|
|
Sign up to set email alerts
|

Overexpression of Cholesteryl Ester Transfer Protein Increases Macrophage-Derived Foam Cell Accumulation in Atherosclerotic Lesions of Transgenic Rabbits

Abstract: High levels of plasma high-density lipoprotein-cholesterol (HDL-C) are inversely associated with the risk of atherosclerosis and other cardiovascular diseases; thus, pharmacological inhibition of cholesteryl ester transfer protein (CETP) is considered to be a therapeutic method of raising HDL-C levels. However, many CETP inhibitors have failed to achieve a clinical benefit despite raising HDL-C. In the study, we generated transgenic (Tg) rabbits that overexpressed the human CETP gene to examine the influence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…For example, many studies have examined the effect of CETP expression in species that do not naturally express this protein, including mice [for example, (40)(41)(42)(43)], rats (44)(45)(46), and pigs (47). One study reported the expression of human CETP in rabbits, a species where CETP is native (48). In these cholesterol-fed rabbits, a 2-fold increase in plasma CETP mass reduced HDL cholesterol by 30%, but it did not change plasma TC or LDL cholesterol or alter atherosclerotic lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…For example, many studies have examined the effect of CETP expression in species that do not naturally express this protein, including mice [for example, (40)(41)(42)(43)], rats (44)(45)(46), and pigs (47). One study reported the expression of human CETP in rabbits, a species where CETP is native (48). In these cholesterol-fed rabbits, a 2-fold increase in plasma CETP mass reduced HDL cholesterol by 30%, but it did not change plasma TC or LDL cholesterol or alter atherosclerotic lesion size.…”
Section: Discussionmentioning
confidence: 99%
“…This direct relationship between amino acid sequence and DNA recognition has made engineering sequence specific binding domains much easier than ZFNs (Boch et al, 2009;Moscou and Bogdanove, 2009). Using TALEN technology, Lai's laboratory at GIBH, immediately generated two kinds of KO rabbits: an immunodeficent KO rabbit with deficiency of Rag1 and Rag2 genes (Song et al, 2013) and fumarylacetoacetate hydrolase deficient rabbits (Li et al, 2017), which mimics human genetic disease tyrosinemia type I, an autosomal recessive disorder caused by mutations in the both copies of the gene encoding the enzyme. Although TALENs are considered superior to ZFNs in terms of fewer off-target effects, easy design and production, it was soon replaced by the CRISPR-Cas9 based genome editing technology, which is even more rapid and modular than the TALEN platform.…”
Section: Knock-out and Knock-in Rabbits By Genome Editing Techniquesmentioning
confidence: 99%
“…[10] Overexpression of CETP might contribute to the development of atherosclerosis by decreasing serum HDL-C levels and increasing the accumulation of macrophage-derived foam cells in lesions. [11] In addition, baseline CETP levels might predict the lipid-reducing effects of statin. [12] CETP inhibitors could increase the serum HDL-C levels and reduce the incidence of diabetes.…”
Section: Introductionmentioning
confidence: 99%